Penerapan Metode Certainty Factor Pada Sistem Pakar Dalam Diagnosa Kerusakan Listrik Rumah Tangga - Rendi Febriyanto; Reno Supardi; Eko Prasetyo Rohmawan (Jurnal Media Infotama, 2024)
PLN is a State-Owned Enterprise (BUMN) with Persero status. PT PLN as a company engaged in the energy sector that provides electricity, electricity support and operational services. Electric power is classified based on its designation, one of which is electricity for households. The community pays little attention to household electrical problems, even though there are many small electrical problems that result in short circuits and fires. This of course must be supported by a good and correct household electrical installation to avoid these electrical problems. The application of the Certainty Factor Method to expert systems in diagnosing household electrical damage can be used as a forum to make it easier for the community to help indicate household electrical damage earlier. The expert system for diagnosing household electrical damage can also be accessed online with internet access via the web link https://kerrusakanlistrik.vad.my.id/, therefore, it makes it easier for the public to conduct consultations regarding the electrical damage they are experiencing. An expert system for diagnosing household electrical damage is made using the PHP programming language and MySQL database. In this expert system, the Certainty Factor Method has been applied which is used to trace household electrical damage based on the symptoms experienced by the community. Based on the system testing that has been done, it can be concluded that the functionality of the application has been running well and this expert system can provide consultation results based on the symptoms selected by the user through the stages of the Certainty Factor (CF) method.